Karakterisasi Dan Kapasitansi Elektroda Karbon Aktif Tempurung Kemiri Dengan Variasi Aktivator Asam Fosfat (H3po4) - Cahyani, Rahmatika Fitri; Nasution, Nazaruddin; Lubis, Ridwan Yusuf (Fakultas Teknik UMSU, 2025)
This research aims to determine the quality of activated carbon used as capacitor electrodes. This research used the basic ingredients of candlenut shells taken at the petalni kemiri walrgal village of Balru Laldalng Balmbu Village. The samples were then tested to determine the effect of varying activator concentration of phosphoric acid (H3PO4) on the characterization and capacitance values in making activated carbon capacitor electrodes. This research was carried out in three stages, namely carbonization, activation and dehydration. The carbonization process at a temperature of 700oC, 90 minutes and chemical activation uses varying concentrations for samples A, B and C, namely 5%, 10% and 15%. The addition of the H3PO4 activator had an influence on the morphological structure of the activated carbon which was tested using SEM, functional groups using the FTIR test and surface area using the Methylen Blue method with UV-Vis as well as the capacitance value of the supercapacitor electrode made with activated carbon and tested with a digital multimeter. The resulting pore diameters were 3.572 µm, 3.894 µm, and 2.7549 µm respectively, with the functional groups O-H, C ≡ N, C ≡ C, and C – Br, and the pore surface area of activated carbon was 16.6018m2/g , 16.8808 m2/g and 16.3050 m2/g. The capacitance values of the candlenut shell activated carbon capacitor electrodes produced were 527.1 µF, 784.1 µF, and 497.4 µF. So the most optimal activated carbon sample is sample B with a 10% H3PO4 variation.